A broadside radiating holographic antenna excited by a traveling wave patch array - Sutinjo, Adrian; Okoniewski, M. (2010)
We present a method of exciting a surface wave based hologram using a traveling-wave microstrip patch array to achieve broadside radiation. This holographic antenna may also be viewed as a periodic surface wave based leaky-wave antenna (LWA) fed by a fundamental mode microstrip LWA. Broadside radiation in the E-plane is achieved by the symmetric holographic surface. In the H-plane, broadside radiation from the patch array is attained by introducing reflection compensation sections in the microstrip line. A beam with peak radiation at broadside in both E and H-planes is achieved with 17.7 dBi antenna gain at approximately 7.7 GHz. ©2010 IEEE.